Characteristics of a Multi-Ethnic Educational Environment in the Republic of Uzbekistan (Based on the Fergana Valley) - Jamoliddinova , Marjona (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This thesis explores the formation and functioning of a multi-ethnic educational environment in the Republic of Uzbekistan, using the Fergana Valley as an example. The relevance of this study stems from the increasing attention paid to issues of intercultural interaction, tolerance, and the effective organization of the educational process in a multi-ethnic society.